Produção textual em língua portuguesa: uma proposta para a construção de textos argumentativos - LUZ, Rakell Ainy Freitas (2020)
This research deals with textual production in Portuguese and aims to present a proposal that favors the construction of an argumentative text, considering the difficulties faced by students in the task of textual production. The investigation was carried out at UEB Sá Valle, and its target audience was students of the 9th grade of the referred institution. It proposed to investigate the teaching of Portuguese language in the context of textual production in order to analyze how the production of texts takes place in that level by students. The investigation focused specifically on identifying the theoretical and methodological concepts that guide textual production practices, verifying in textual compositions the main difficulties faced by students in the act of writing, and also elaborating, through the systematization of ideas, a theoretical and methodological proposal that may contribute to the production of an argumentative text. In order to achieve these objectives, we used the theoretical contributions of Koch and Elias (2017), Perelman (2005), Fiorin (2018), Faria (2009), Koch (2008), Koch and Elias (2016), Reboul (2004 ), Aristotle (2005), Aranha (2010), Koch (1997), Plantin (2008), Amossy (2018), Koch (1987), Suarez (2002), Cavalcante (2018), Angelim (1996), Bronckart (1999), Adam (2019). Therefore, we conducted a study with a qualitative approach, using the bibliographic survey and interviews for this. In addition to bibliographic and documentary research, we chose to do a field research through which the collected data were duly recorded in a field diary. We also used as a procedure an instrumental case study in order to intervene in the solution of the investigated problem through the product we had elaborated and applied. Thus, we proved that even with the obstacles the task of writing imposed, it was possible to enable students to build an argumentative text without so many difficulties through the use of systematization of ideas.